Deteksi Dini Kanker Serviks Dengan Inspeksi Visual Asam (IVA) - Yessy Nur Endah Sary; Tutik Ekasari; Homsiatur Rohmatin; Iit Ermawati (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
Cervical cancer is one of the most common causes of cancer. The incidence of cervical cancer and death from cervical cancer continues to increase worldwide. This community service activity was carried out at the Darul Ulum Foundation, Patokan, Probolinggo Regency with respondents namely women of childbearing age. The purpose of this community service activity is to provide information to women of childbearing age about the importance of early detection of cervical cancer. This activity begins with a pre-test to measure respondents' knowledge about early detection of cervical cancer, then provides health education and ends with a post-test to measure respondents' knowledge about early detection of cervical cancer after providing health education. By providing Health Education, it is hoped that respondents will become self-aware and motivated to carry out early detection by participating in an Acid Visual Inspection (IVA) at the nearest Health Center.